Narrative Review: The Effect of Counseling on Adherence in Patients with Type 2 Diabetes Mellitus - Gandis Larasati; Diana Ramatillah; Kashif Khan (Sciences and Clinical Pharmacy Research Journal, 2026)
This study aimed to evaluate the effect of counseling on medication adherence among patients with type 2 diabetes mellitus through a narrative review of 50 national and international articles published between 2020 and 2025. The narrative review method was conducted by selecting journals from Elsevier, MDPI, PubMed, SpringerLink, Wiley, as well as nationally indexed SINTA journals using relevant keywords.The results of the review indicate that pharmacist-led interventions through counseling, including brief counseling, home pharmacy care, and digital media–based education, consistently improved patient knowledge, enhanced medication adherence, and reduced clinical parameters such as blood glucose levels, HbA1c, and HOMA-IR. These interventions also improved patients’ quality of life and disease perception.Based on these findings, it can be concluded that pharmacist-led interventions through structured counseling and pharmaceutical education have a significant positive impact on the management of type 2 diabetes mellitus, particularly in improving patient knowledge, disease perception, and adherence to therapy. Improvements in therapeutic behavior directly contributed to better clinical outcomes, including reductions in blood glucose, HbA1c, HOMA-IR, body weight, and waist circumference after 90 days of intervention. The greatest effects were observed in patients with HbA1c levels > 9%, indicating that high-risk groups derived the greatest benefit from pharmacist involvement in the management of type 2 diabetes mellitus.Future studies are recommended to evaluate the long-term effects of counseling and to standardize adherence assessment instruments. Strengthening pharmaceutical care policies is also recommended to improve the quality and consistency of counseling services and to develop sustainable intervention models in primary healthcare settings.